(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
The concept of metaverse brought into discussion these days in the context of rebrands of the social network Facebook under the name Meta, raises questions on several levels, both in terms of cybersecurity and in terms of human rights. This term metaverse first appears in 1992 in the novel Snow Crash by Neil Stephenson, an American writer of speculative fiction, and it describes the virtual reality that exists alongside physical reality, a parallel coexistence. This meta, originally from the Greek language („with”, „after”, „next”, „above” and „beyond”) expresses a reality „from beyond” leading to the idea of metamorphosis, a change of place or state . Mark Zuckerberg, the Facebook company’s CEO, imagines his metaverse as a virtual space that uses digital tools to offer a sense of physical presence to all over the world people. If Zuckerberg’s prediction will become a reality, it is clear that the cyber security protection will need to increase accordingly. The metaverse will enter and will penetrate our private life and it will dramatically impact our human rights. This intersection between metaverse and cybersecurity, on the one hand, and human rights, on the other, will be examined in this article.